Irony Expressed by Adjectives and Verbs in English Literature - Mavlonova Ugiloy Khamdamovna (Researchparks Publishing, 2022)
In the article, the translation of “The Master and Margarita” by Russian writer Mikhail Bulgakov is studied by several translators with an in-depth analysis of examples of irony expressed by adjectives and verbs.